2022
DOI: 10.1186/s12884-022-04704-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the predictive value of fetal Doppler indices and neonatal outcome in late-onset preeclampsia with severe features: a cross-sectional study in a resource-limited setting

Abstract: Background Preeclampsia constitutes a major health problem with substantial maternal and perinatal morbidity and mortality. The aim of this study was to detect the diagnostic efficacy of fetal Doppler in predicting adverse outcomes in severe late onset preeclampsia (LOP). Methods A prospective study was conducted among childbearing women who presented with severe LOP and matched controls. Umbilical artery (UA) and middle cerebral artery (MCA) Doppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…[18][19][20][21] In their study, Moawad et al compared various fetal Doppler parameters in late-onset preeclampsia with severe features and found that UA Doppler is still an effective method for unfavorable birth outcomes and disease management. 22 Our study has some limitations. Although our study emphasizes the importance of CPUR in preeclampsia, more comprehensive results will be obtained with larger series and prospective studies that include neonatal blood gas parameters.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…[18][19][20][21] In their study, Moawad et al compared various fetal Doppler parameters in late-onset preeclampsia with severe features and found that UA Doppler is still an effective method for unfavorable birth outcomes and disease management. 22 Our study has some limitations. Although our study emphasizes the importance of CPUR in preeclampsia, more comprehensive results will be obtained with larger series and prospective studies that include neonatal blood gas parameters.…”
Section: Discussionmentioning
confidence: 89%
“…Uterine artery Doppler, umbilical artery Doppler and middle cerebral artery Doppler, and cerebroplacental ratio have been studied exclusively to predict disease severity and unfavorable perinatal outcome in conditions associated with placental insufficiency 18–21 . In their study, Moawad et al compared various fetal Doppler parameters in late‐onset preeclampsia with severe features and found that UA Doppler is still an effective method for unfavorable birth outcomes and disease management 22 . However, of the individual parameters, only the CPR index was found to be the best index for predicting such outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Moawad et al found that fetal doppler parameters are associated with late onset (>34 weeks) preeclampsia and determined poor neonatal outcomes. 12 Piotr et al studied the link between angiogenesis markers in maternal blood including anti-angiogenic factor soluble fms-like tyrosine kinase-1 (sFlt-1) and pro-angiogenic factor, placental growth factor (PlGF) and its impact on neonatal outcomes. [13][14][15] It was found that a high sFlt-1/PlGF before 32 weeks GA was associated with significant increase in adverse neonatal outcomes including respiratory distress syndrome, patent ductus arteriosus, sepsis, intreventricular hemorrhage, retinopathy of prematurity and bronchopulmonary dysplasia.…”
Section: Discussionmentioning
confidence: 99%